Preparation, characterization, and swelling behaviour of superabsorbent hydrogel from semi-refined kappa carrageenan crosslinked with acrylic acid - Nor Shuhadah binti Warzukni (Kulliyyah of Science, International Islamic University Malaysia, 2015)
This study was carried out to use a natural-based material, semi-refined κ-carrageenan which is easier to produce as compared to refined κ-carrageenan in the preparation of superabsorbent polymer (SAP) hydrogel. The production of semi-refined and refined κ-carrageenan from local red seaweed, Kappahycus alvarezii (Doty) Doty ex P. Silva were done to provide natural polymer for the preparation of SAP hydrogel. Red seaweed was treated with alkaline solution to produce semi-refined κ-carrageenan while refined κ-carrageenan was produced through gelling, freeze-thawing and alcohol precipitation process. The percentage yields of semi-refined and refined κ-carrageenan were 62.2 % and 59.0 %, respectively. For the preparation of semi-refined κ-carrageenan-graft-poly(acrylic acid) (SRκC-g-PAA) hydrogel, semi-refined κ-carrageenan and acrylic acid were crosslinked through a graft copolymerization method in the presence of N,N-methylene bis-acrylamide as a crosslinker and ammonium persulphate as an initiator. Grafting conditions and alkaline hydrolysis that influenced the swelling of the hydrogel were optimized to achieve SRκC-g-PAA with high water absorbency. The characterization of the hydrogel was investigated using different techniques such as FTIR spectroscopy, SEM microscopy, measurement of swelling capacity, swelling kinetics and centrifuge retention capacity. One-way ANOVA statistical method was used to compare the swelling capacity of SRκC-g-PAA hydrogel with the refined κ-carrageenan-graft-poly(acrylic acid) (RκC-g-PAA) and commercial polyacrylate SAP hydrogels.IR spectrum of the SRκC-g-PAA indicated the formation of graft copolymer product. SEM microscopy suggested that the hydrogel exhibited a compact structure with porous properties. In swelling capacity measurement, it was found that the absorbency of SRκC-g-PAA in salt solutions was affected by the charge of cations from the external solutions. The equilibrium swelling capacity of SRκC-g-PAA hydrogel was higher than the equilibrium swelling capacity of RκC-g-PAA and commercial polyacrylate SAP hydrogels in 0.15 M KCl and 0.15 M CaCl2 solution(p < 0.05). Swelling capacity in 0.5 M NaCl showed there was no significant different between the hydrogels. The equilibrium swelling capacity of SRκC-g-PAA was higher than the equilibrium swelling capacity of RκC-g-PAA hydrogel at pH 7 and pH 9 (p < 0.05). However, there was no significant different in terms of swelling capacity between the SRκC-g-PAA, RκC-g-PAA and commercial polyacrylate SAP hydrogels in other pH solutions. Moreover, there was no significant different in terms of swelling capacity between the SRκC-g-PAA and RκC-g-PAA in synthetic urine solution, and the swelling capacity between the SRκC-g-PAA, RκC-g-PAA and commercial polyacrylate SAP in synthetic serum solution. Therefore, it was suggested that the SRκC-g-PAA has higher or equivalent swelling capacities than the RκC-g-PAA and commercial polyacrylate SAP in various aqueous solutions. Additionally, the swelling kinetics and centrifuge retention capacity measurement at specific time intervals were carried out to measure the rate of absorbency of the SRκC-g-PAA and its ability to retain water when mechanical pressure was applied on it. It showed that the swelling rate of the hydrogel was influenced by external solutions and it can retain at least 80% of absorbed aqueous solutions.